Analysis of plant genes involved in aromatic volatile production - Wongs-Aree, Chalermchai (2003)
The cDNA CM-AATI from melon was expressed as a fusion protein in yeast, Saccharomyces cerevisiae. The protein exhibited alcohol acyl-transferase (AAT) activity, producing ester compounds from a wide range of alcohols and acyl-CoAs. A second cDNA clone, Le-AAT1 was identified by heterologous screening of a tomato fruit library with the melon CM-AAT1 probe. The amino acid sequence of the encoded protein showed some similarities to many proteins using acyl-CoAs as substrates, including CM-AAT1. The Le-AAT1 open reading frame (ORF) consists of 1329 nucleotides, encoding 442 amino acids, while the CM-AATI ORF is 1431 nucleotides in length with a deduced sequence of 476 amino acids. Although the Le-AAT1 showed 43% identity to the CM-AAT1 at the amino acid level, the yeast expressed protein demonstrated AAT activity. On the other hand, a second melon clone, CM-AAT2, encoding a 475 amino acid protein, which is 86% identical to the CM-AAT1 protein, did not show AAT activity. The CM-AAT1 fusion protein was active over pH 6.0 to pH 8.0 in vitro with activity being enhanced by Mg2+, whereas the Le-AAT1 protein performed efficiently at pH between 6.0 and 9.0 with Na+. The activity of the CM-AAT1 protein probably requires posttranslational modifications since the protein expressed in Escherichia coli was inactive.